Clinical Assessment of Nursing Care Regarding Prevention of Ventilator-associated Pneumonia in Neonates - Leila Khanali Mojen; Maryam Rassouli; Saleheh Tajalli; Ahmad Reza Baghestani; Zahra Jafari (Mashhad University of Medical Sciences, 2019)
Background: Ventilator-associated pneumonia (VAP) is the second common nosocomial infection in NICUs leading to some complications. Nurses are one of the main resources in health care that directly influence neonatal health care. Responsibility of most of preventive strategies related to VAP complications lies with nurses; therefore, nursing care should be assessed until the nurses show standard level of performance in hospitals. The aim of this cross-sectional study, conducted within 2015-2016, was to assess nursing care regarding VAP prevention in neonatal intensive care units (NICUs) in selected hospitals affiliated to Shahid Beheshti University of Medical Sciences. Methods: In this descriptive cross-sectional study, 100 observations of nursing care regarding VAP were selected by convenience method in NICUs of Mahdiyeh, Mofid, and Imam Hossein hospitals affiliated to Shahid Beheshti University of Medical Sciences within 2015-2016. The data collection tools included demographic information questionnaire and a developed checklist related to VAP prevention. The observations were assessed and documented with two sampling methods, including time and event sampling. The data were analyzed in SPSS software (version 16). Results: According to the results of the current study, the rate of compliance of nursing care with the standards for prevention of VAP in neonates under mechanical ventilation in NICU with developed standards was estimated at 62.81 percent. Conclusion: Authorities should pay more attention to nursing cares especially incompetent cares explained in this study to increase the health of hospitalized neonates, decrease complications, length of stay, and costs. Moreover, future research is needed to investigate the reasons of this incompetency.